2019
DOI: 10.4103/aian.aian_321_18
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated strongyloidiasis: Breaking brain barriers

Abstract: Strongyloides stercoralis (SS) is one of the most overlooked helminthic infections despite being highly endemic in tropical and subtropical areas. In immunocompromised patients, especially those on long-term steroids, infection can often escalate to fatal dissemination into major organs. We present a compendium of two immunocompromised patients, who were on high-dose steroids and presented with worsening neurological status. Cerebrospinal fluid analysis was notable for larvae of SS as diagnosed by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…Disseminated strongyloidiasis afecting the brain and meninges is rare, but some cases have been described in the literature sometimes only with postmortem diagnosis; in some cases, central nervous system (CNS) invasion is documented antemortem by isolation of S. stercoralis larvae in CSF or brain [14][15][16][17][18][19]. In our frst case, even though no distinct larval forms were observed in CSF samples, CNS involvement was presumed due to PCR detection of S. stercoralis nucleic acids in the patient's CSF and unexplained prolonged encephalopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Disseminated strongyloidiasis afecting the brain and meninges is rare, but some cases have been described in the literature sometimes only with postmortem diagnosis; in some cases, central nervous system (CNS) invasion is documented antemortem by isolation of S. stercoralis larvae in CSF or brain [14][15][16][17][18][19]. In our frst case, even though no distinct larval forms were observed in CSF samples, CNS involvement was presumed due to PCR detection of S. stercoralis nucleic acids in the patient's CSF and unexplained prolonged encephalopathy.…”
Section: Discussionmentioning
confidence: 99%
“…This testing, although seemingly necessary at the time, could have been avoided by evaluating the most likely risk factors based on his demographic information. Sebastian et al also found that the lifetime prevalence of parasitic infections in southern India could be as high as 97% [ 9 ]. Therefore, the patient could have avoided excessive testing and a reduced risk of overtreatment [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…A closer evaluation of the patient鈥檚 demographic profile and his immigration status from India meant that there was a possibility of a clinically latent parasitic infection. Sebastian et al found that among asymptomatic individuals in various parts of southern and northern India, the prevalence of Strongyloides ranged from 20% to higher than 90% [ 9 ]. The decision was then made to test for parasitic infections, and Strongyloides O&P (ova and parasite), as well as anti-Strongyloides IgG, were both positive.…”
Section: Case Presentationmentioning
confidence: 99%
See 1 more Smart Citation